2021
DOI: 10.3389/fgene.2021.724625
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence Quotient Variability in Klinefelter Syndrome Is Associated With GTPBP6 Expression Under Regulation of X-Chromosome Inactivation Pattern

Abstract: Klinefelter syndrome (KS) displays a broad dysmorphological, endocrinological, and neuropsychological clinical spectrum. We hypothesized that the neurocognitive dysfunction present in KS relies on an imbalance in X-chromosome gene expression. Thus, the X-chromosome inactivation (XCI) pattern and neurocognitive X-linked gene expression were tested and correlated with intelligence quotient (IQ) scores. We evaluated 11 KS patients by (a) IQ assessment, (b) analyzing the XCI patterns using both HUMARA and ZDHHC15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
3
0
1
Order By: Relevance
“…Additionally, intellectual disability was assessed in 57.1% of the patients. Similarly, Simonetti et al, [23] recorded intellectual disability present in KF relies on an imbalance in X-chromosome gene expression. On the other hand, it was reported that the majority of subjects with 47, XXY karyotype have a normal intellectual level [24].…”
Section: Discussionmentioning
confidence: 81%
“…Additionally, intellectual disability was assessed in 57.1% of the patients. Similarly, Simonetti et al, [23] recorded intellectual disability present in KF relies on an imbalance in X-chromosome gene expression. On the other hand, it was reported that the majority of subjects with 47, XXY karyotype have a normal intellectual level [24].…”
Section: Discussionmentioning
confidence: 81%
“…Класична форма синдрому Клайнфельтера, яка наявна у 80-90 % випадків, визначається каріотипом 47,XXY унаслідок анеуплоїдії статевих хромосом, тоді як анеуплоїдії вищого ступеня (наприклад, 48,XXXY або 48,XXYY), структурно аномальна Х-хромосома (наприклад, 47,iXq,Y) або мозаїцизм (наприклад, 47,XXY/46,XY) становлять решту 10-20 % випадків [2][3][4][5].…”
Section: вступunclassified
“…GTPBP6 was found to be among differentially expressed X-linked genes in an association study of verbal cognition defects in a group of Klinefelter's Syndrome (KS) individuals [203]. Both GTPBP6 and SYBL1 (encoding VAMP7) are involved in cognitive development, and GTPBP6 expression has been found negatively associated with full-scale intelligent quotient (IQ) under the regulation of the type of X-chromosome inactivation (XCI) pattern [204].…”
Section: Other Trafficking Factorsmentioning
confidence: 99%